Obstetric, foetal and neonatal outcomes in adolescent pregnancy in sub-Saharan Africa: Systematic review and meta-analysis protocol - Anthony Danso-Appiah; Eric Behene; Joan Naadu Hazel; Shirley Abanga (PLoS ONE, 2025)
Background Teenage pregnancy remains an important public health challenge in sub-Saharan Africa (SSA), with significant adverse health outcomes for the mother, their foetuses and infants. This systematic review will assess the impact of teenage or adolescent pregnancy on maternal obstetric, foetal and infant health outcomes, with the aim to inform evidence-based implementation of context-sensitive interventions and policies across countries in SSA. Methods This protocol has been informed by the Cochrane handbook and other published works and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for protocols (PRISMA-P) guidelines. We will search CINAHL, PubMed, Google Scholar, Scopus, Web of Science, Cochrane Library and LILACS, from inception to April 30, 2025, without language restriction. The search terms include ‘teenage pregnancy’, ‘adolescent pregnancy’, ‘maternal outcomes’, ‘obstetric outcomes’, ‘maternal death’, ‘maternal mortality’, ‘foetal outcomes’, ‘infant outcomes’ and ‘APGAR score’, together with their synonyms or alternate words, American or British spelling, singular or plural forms of the search terms or concepts. The names of all the 48 countries in SSA will be included as search terms. We will also search HINARI, African Journals Online, conference proceedings, preprint repositories, database of thesis, Specialized Obstetrics and World Bank Open Knowledge Repositories, WHO, PATH, and UNICEF databases. We will review the reference lists of relevant papers, and where necessary, contact experts in the field for their knowledge about studies missed by our searches. The retrieved studies will be managed in Endnote version X9 and duplicates removed. The deduplicated studies will be exported to Rayyan for study selection. At least two reviewers will independently screen and select studies using pre-tested study selection flow chart developed from the pre-specified eligibility criteria, extract the data using pretested data extraction form, and assess risk of bias in the included studies using ROBINS-E for non-randomized studies of exposure effects. Any disagreements will be resolved through discussion among the reviewers. We will analyze continuous outcomes as mean difference (MD) for studies using the same scales with their standard deviation (SD) and for studies measuring outcomes on different scales, the standardized mean difference (SMD) will be used. Binary/dichotomous outcome data will be expressed as odds ratio (OR) or risk ratio (RR). All the effect measures will be presented with their 95% confidence intervals (CIs). Pooled proportions will be used to determine prevalence or incidence of specific maternal, foetal and infant health outcomes. Heterogeneity will be assessed graphically and quantitatively using the I2 statistic. Random-effects meta-analysis will be used to synthesize data from the included studies, expected to be heterogeneous and with varying effect sizes. Where data permits, we will conduct subgroup analysis on key factors such age, trimester, gestation at delivery etc. to address the sources of heterogeneity. Where possible, sensitivity analysis will be performed to test the robustness of the pooled estimates around outlier variables and key risk of bias domains. The Grading of Recommendations Assessment Development and Evaluation (GRADE) approach will be used to assess the overall certainty of the evidence generated. Expected outcomes This systematic review will inspire countries in Sub-Saharan Africa to implement innovative and context-sensitive programs that will improve the health and outcomes of adolescent pregnancy. An important step toward achieving this is to collate all empirical data through robust systematic review and meta-analysis to distill evidence at the highest level possible. Being the first review to rigorously identify and assess teenage pregnancy-related obstetric, foetal, and neonatal outcomes through the antenatal, labour to post-delivery (post-partum) periods within SSA, the review’s key findings will provide important evidence that will support efforts towards improving the wellbeing of teenage mothers and their newborns. Additionally, in countries across SSA where adolescent pregnancy rates are high and healthcare systems are constrained, this study may highlight important knowledge gaps that can be crucial in directing future research and resource allocation, for example, identifying the subgroup that will benefit from the limited resources. Also, the accumulated data to be pooled from these countries can shed light on the key factors influencing pregnancy outcomes and the trimesters during which these young mothers and their foetuses are most at risk and vulnerable. Such knowledge can help inform future policies and clinical practice. Protocol registration This systematic review protocol has been registered in PROSPERO [CRD42024575044].